DEVELOPMENT OF NON-PROFIT ACCOUNTING INFORMATION SYSTEMS - Carolina Lita Permatasari; Dwi Iga Luhsasi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2022)
This research is included in information system development research. The output product of this research is an Accounting Information System. The stages used in this study adapt the waterfall model from Pressman. Implementation of web-based system development using MySQL database on PHPMyAdmin. MySQL is one of the Database Management System (DBMS). The backend development of the accounting information system of this non-profit organization focuses on system logic starting from input, process and output. Input financial transactions in cash and bank as well as transactions that affect capital excluding income and costs. Automatically processes the inputted data in the report recapitulation according to the primary key that is set. Cash, bank, and capital transaction inputs are automatically recorded in the cash, bank and capital ledger, income ledger, expense ledger, income details, expense details, cash flow, and year-end reports. The output of the inputted report is a print preview to print the report by connecting to the hardware (printer). The testing procedure in this study was carried out with 2 tests, namely white-box testing, testing of the buttons on the system and black-box testing, testing of functions or processes that occur in the system. The data obtained from the results of filling out a set of instruments in the form of a questionnaire given to experts and users to assess the feasibility of the developed system. The results of the development research state that the accounting information system for non-profit organizations is feasible to be applied. This is evidenced by the results of the validation test of material experts, technology experts, and trials to users who are in the outstanding categories. The average on the material expert validation test shows the outstanding category with a score of 4.8. Technology experts show the outstanding category with a score of 4.78. Meanwhile, the trials on users belong to the very good category with a score of 4.7.